Development and Evaluation of Digital Learning Materials for Arabic Reading Skills Using a Scientific Approach in Islamic Elementary Schools - Malikh, Majda Qudsiyatul; Mubaligh, Ahmad; Fitriani, Laily (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
Mastering maharah qiraah in Arabic learning is crucial as it is the gateway to understanding Arabic texts, which are key sources of Islamic knowledge. The scientific approach has enhanced students' comprehension, making developing effective teaching materials essential. This study develops and evaluates "Dila Baca," a digital Arabic reading teaching material based on a scientific approach. Utilizing the ADDIE model, this research involved 52 students and two experts. Validation results show a high level of feasibility (90%), and statistical tests indicate significant learning improvements (Sig. 0.024 < 0.05; N-gain: 77.1%). The findings highlight the effectiveness of "Dila Baca" in enhancing Arabic reading comprehension through interactive e-learning materials.